2007
DOI: 10.1038/sj.gene.6364452
|View full text |Cite
|
Sign up to set email alerts
|

The common variants of E-selectin gene in Graves’ disease

Abstract: Adhesion molecules are involved in cell invasion in autoimmune thyroid disease. It was also reported that patients with untreated Graves' disease (GD) had high serum level of soluble form of E-selectin (sE-selectin), the concentration of which correlated with the activity of the disease. The aim of the present study was to elucidate whether the common variants in Eselectin gene (SELE) were associated with the development of GD. Six tagSNPs within SELE were studied in 297 patients with GD and 208 healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The Ser128Arg gene variant, the most commonly reported SELE-gene polymorphism, is associated with a wide variety of disorders, including coronary artery disease, venous thrombosis, ischemic cerebral vascular disease, postoperative myocardial infarction, prognosis of colorectal cancer, restenosis after successful coronary angioplasty, severity of atherosclerotic arterial disease, peripheral arterial occlusive disease, and coronary calcification [8-12]. Common variants of the SELE gene have also been found associated with the susceptibility to either Graves’ disease or hypertension [13-15]. However, the association between SELE SNPs and E-selectin levels has been controversial [15-17], and the association between SELE SNPs and other inflammatory marker levels has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ser128Arg gene variant, the most commonly reported SELE-gene polymorphism, is associated with a wide variety of disorders, including coronary artery disease, venous thrombosis, ischemic cerebral vascular disease, postoperative myocardial infarction, prognosis of colorectal cancer, restenosis after successful coronary angioplasty, severity of atherosclerotic arterial disease, peripheral arterial occlusive disease, and coronary calcification [8-12]. Common variants of the SELE gene have also been found associated with the susceptibility to either Graves’ disease or hypertension [13-15]. However, the association between SELE SNPs and E-selectin levels has been controversial [15-17], and the association between SELE SNPs and other inflammatory marker levels has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Common variants of the SELE gene have also been found associated with the susceptibility to either Graves’ disease or hypertension [13-15]. However, the association between SELE SNPs and E-selectin levels has been controversial [15-17], and the association between SELE SNPs and other inflammatory marker levels has not been reported. This investigation aimed to elucidate the association between SELE SNPs and the plasma levels of sE-selectin and MMP9, in Taiwanese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge only 1 previous study has used similar techniques to identify 6 tagging SNPs [21] and also did not identify A561C as a tagging SNP. Two tagging SNPs identified by HapMap analysis were selected for further study (rs3917417 G2692A and rs3917454 C1901T).…”
Section: Introductionmentioning
confidence: 99%
“…[112,113]. Chen H, et al [114,115] reported common L-selectin or E-selectin variants may be associated with susceptibility to Graves' disease in Chinese population. Cytokines, a large group of non-enzymatic proteins, participate in the induction and effector phases of all inflammatory and immune responses, and are therefore likely to play a critical role in the development of autoimmune diseases [116].…”
Section: Hyperthyroidismmentioning
confidence: 99%